End-of-Life Acceptance in Hemodialysis Patients: A Conceptual Analysis - Wabula, La Rakhmat; Yetti, Krisna; Masfuri, Masfuri; Widyatuti, Widyatuti; Widyawati, Ika Yuni; Septiwi, Cahyu (Journal of Health and Nutrition Research, 2025)
End-of-life (EOL) acceptance is a crucial but underexplored concept among patients with end-stage renal disease (ESRD) undergoing hemodialysis. This study aimed to analyze and clarify the concept of EOL acceptance in hemodialysis patients using Walker and Avant’s eight-step method. These patients often face progressive physical deterioration and limited life expectancy, making psychological, emotional, and spiritual readiness to confront death a fundamental component of care. However, the term “EOL acceptance” lacks conceptual clarity and consistency in nursing practice. A comprehensive literature review was conducted using PubMed, CINAHL, and Scopus databases, targeting studies published between 2014 and 2024. The keywords used included ‘end-of-life,’ ‘terminal care,’ ‘death acceptance,’ ‘dying acceptance,’ ‘hemodialysis,’ ‘end-stage renal disease,’ and ‘terminal care nursing’. The analysis identified three attributes of EOL acceptance:  psychological readiness to face death, integration of existential and spiritual meaning, and proactive decision-making toward dignified dying. Supporting factors include awareness of terminal illness, therapeutic communication, and psychosocial-spiritual support. The identified consequences are emotional peace, enhanced family preparation, and improved quality of life. This analysis delineates a conceptual framework for EOL acceptance, enabling nurses to assess and support patients facing terminal illness effectively. It also provides a foundational framework for developing assessment tools and nursing interventions to improve person-centered EOL care for individuals with ERSD.